Age-related changes in CD4+ T and NK cell compartments may contribute to the occurrence of pregnancy loss in advanced maternal age. (February 2023) - Muyayalo, Kahindo P.; Tao, Ding; Lin, Xin-Xiu; Zhang, Yu-Jing
Abstract: A recent study characterized novel immune cell subsets (T, NK, and γδ T cell subsets) related to recurrent pregnancy loss (RPL). This study aims to assess whether these RPL-related immune cell subsets are affected by aging. The percentages of peripheral blood immunes cells from nulligravida women (NGW), women with a history of normal pregnancy (NP), and women with a history of pregnancy loss (PL) were detected by flow cytometry. The correlations between maternal age and cell percentages were assessed. We found a significant positive correlation between PL and maternal age. The percentages of effector memory CD4 + T (CD3 + CD4 + CD45RA¯ CCR7¯), terminally differentiated CD4 + T (CD3 + CD4 + CD45RA + CCR7¯), and mature NK cells (CD3¯ CD56 +lo ) significantly increased with maternal age. A significant decrease in the percentage of Naïve CD4 + T cells (CD3 + CD4 + CD45RA + CCR7 + ) with age was observed in women from the NP group. Women aged 35 or older had significantly higher percentages of effector memory CD4 + T cells, terminally differentiated CD4 + T cells, and mature NK cells than younger women. Maternal age positively correlates with terminally differentiated CD4 + T, effector memory CD4 + T, and mature NK cell percentages. In contrast, an inverse correlation was observed between Naïve CD4 + T cell and age among women from the NP group. Our findings indicate that age-related CD4 + T and NK cell dysregulation might be involved in the pathogenesis of PL in women with advanced maternal age. The underlying mechanism needs further investigation. Highlights: Pregnancy loss and its recurrence (RPL) significantly increase with maternal age. Memory CD4 + T and mature NK cells are differentially expressed in RPL patients. Memory CD4 + T and mature NK cells also significantly change with aging. Age-related changes in CD4 + T and NK cells may be involved at least partially in PL.